PENGEMBANGAN BAHAN AJAR DIGITAL PAI DALAM MENUNJANG KEBUTUHANDAN KEMUDAHAN BELAJAR PESERTA DIDIK DI MTs AL-ISLAM TELAGA BIRU KABUPATEN GORONTALO - Safia, Elvia; Hasani, Dewi Nursafitri S; Hulinggi, Maryam; Solong, Najamuddin Petta (Universitas Islam Negeri Sumatera Utara Medan, 2024)
Development of PAI digital teaching materials at MTs. Al-Islam Limboto Gorontalo Regency aims to support the needs and ease of learning for students. Fulfilling quality learning needs greatly determines the success of education as a whole, especially in providing ease of learning to students effectively and efficiently. This study used qualitative research methods. The data collection techniques used were observation, interviews and documentation techniques. Research results at MTs. Al-Islam pointed out that the development of PAI digital teaching materials supports the needs and ease of learning for students at MTs. Al-Islam has been implemented well. Thus, educators' efforts to meet the needs and convenience of students can be realized as they should and can enable the learning process in the future to be further improved.